Discovering the Treasure of Public Speaking Member Project Guide - Emily Eubanks; Joy Cantrell Jordan (EDIS)
Discovering the Treasure of Pubic Speaking Member Project Guide (4H PUM 10) is a communication and expressive arts and sciences publication for 4-H members ages 10 and over. The guide teaches members how to pick the purpose of their speech how to collect the information and even tips on how to give a speech. This information was published October 2004 by the Florida Cooperative Extension Service. Revised: September 2005.